PERAN POLA ASUH ORANGTUA DALAM MENDUKUNG PRESTASI NON AKADEMIK ANAK TUNARUNGU: STUDI KASUS DI SLB NEGERI PURBALINGGA - Nur'aeni Nur'aeni; Yulindra Sukma Dewanti; Herdian Herdian; Fatin Rohmah Wahidah (UNS Press, 2025)
Deaf children face challenges in communication, socialization, and potential development. However, with appropriate parenting styles, they can still achieve success in non-academic fields. This study aims to examine the parenting styles applied to children with special needs (deaf) who have achieved national-level non-academic accomplishments at SLB Negeri (Statae Special Education School) Purbalingga. The research uses a qualitative method with a case study approach to understand the lived experiences of individuals. Data were collected through in-depth interviews, observations, and documentation. The results show that a democratic parenting style is the most commonly applied by parents. This style is marked by active parental involvement, the use of positive reinforcement, and a balance between freedom and guided authority, all of which contribute to building the childs self-confidence. Effective communication between parents and children is also crucial for mutual understanding. Additionally, parents emphasize moral and value-based education with discipline that avoids physical or verbal punishment. Collaboration among parents, families, and schools plays a key role in supporting the child's growth. In conclusion, appropriate parenting styles can significantly support children with special needs in developing their full potential.